2017
DOI: 10.1136/bmjopen-2017-017569
|View full text |Cite
|
Sign up to set email alerts
|

Collective leadership and safety cultures (Co-Lead): protocol for a mixed-methods pilot evaluation of the impact of a co-designed collective leadership intervention on team performance and safety culture in a hospital group in Ireland

Abstract: IntroductionThere is accumulating evidence implicating the role of leadership in system failures that have resulted in a range of errors in healthcare, from misdiagnoses to failures to recognise and respond to patient deterioration. This has led to concerns about traditional hierarchical leadership structures and created an interest in the development of collective ways of working that distribute leadership roles and responsibilities across team members. Such collective leadership approaches have been associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…It is anticipated that the network or group will encourage learning across the hospitals in the group and will result in standardization and improvements in access to quality care. The results presented in this paper are part of a larger study and research programme [ 21 ], and the data reported herein are used to highlight the value of SNA in health systems research, and illustrate the types of useful and practical information that may be drawn from the resulting analysis.…”
Section: Methodsmentioning
confidence: 99%
“…It is anticipated that the network or group will encourage learning across the hospitals in the group and will result in standardization and improvements in access to quality care. The results presented in this paper are part of a larger study and research programme [ 21 ], and the data reported herein are used to highlight the value of SNA in health systems research, and illustrate the types of useful and practical information that may be drawn from the resulting analysis.…”
Section: Methodsmentioning
confidence: 99%
“…19,20 The co-design process evaluated in this study is part of a larger research programme on Collective Leadership and Safety Culture (Co-Lead), which aims to introduce collective leadership to healthcare teams to improve team performance and patient safety culture. 21 The objective of the co-design process was to produce a team-based intervention to develop collective leadership competencies within health-care teams. Introducing a leadership model through team-based training differs from traditional leadership development approaches, and there is little existing knowledge on how best to deliver such an intervention.…”
Section: Bymentioning
confidence: 99%
“…The co‐design process evaluated in this study is part of a larger research programme on Collective Leadership and Safety Culture (Co‐Lead), which aims to introduce collective leadership to health‐care teams to improve team performance and patient safety culture . The objective of the co‐design process was to produce a team‐based intervention to develop collective leadership competencies within health‐care teams.…”
Section: Introductionmentioning
confidence: 99%
“…This study is part of a wider research programme on Collective Leadership and Safety Culture (Co-Lead) which aims to introduce collective leadership to healthcare teams across one hospital group to improve team performance and patient safety culture [ 16 ]. In contrast to traditional approaches that focus development on the individual as leader, the approach in this programme is on developing the team as a dynamic leadership entity, ensuring all members understand and develop the capability for leadership.…”
Section: Introductionmentioning
confidence: 99%